Investigating first‐year graduate paramedics' reason for current work location: A cross‐sectional, data linkage study. (7th September 2021) - Ivec, Nicola; Beauchamp, Alison; Sutton, Keith; Mitchell, Eleanor; O'Meara, Peter; Bowles, Kelly‐Ann; Williams, Brett
Abstract: Objective: This study aims to describe the demographic and employment characteristics of first‐year graduates from a Victorian‐based paramedicine course and investigate factors that influenced their choice in place of practice. Design: Cross‐sectional study using data from the Nursing and Allied Health Graduate Outcomes Tracking study. Setting: Victoria, Australia. Participants: First‐year graduates (2019) from the Monash University range of paramedicine programs. Main outcome measures: Variables of interest included principal place of practice and the reasons for working in the current location. Results: Over half of the 2018 paramedicine course graduates responded to the 2019 Graduate Outcomes Survey. Nearly all were registered as paramedics (including double registrants as nurses), and over a fifth were from a rural background; however, less than that were working in a rural area. Of those with complete data, the most cited reasons for current work location were 'spouse/partner's employment or career', 'opportunity for career advancement' and 'scope of practice within the role'. Conclusion: This study provides important insight into the factors associated with rural practice location amongst paramedicine graduates, specifically rural origin or personal, lifestyle and professional influences. The study adds to the sparse literature about paramedic practice location decision‐making and highlights the need for further systematic longitudinal research examining the 'where' and 'why'.